SUJEITOS EM CONFLITO: ANARQUISMO E NACIONALIDADE EM UM AMOR ANARQUISTA - Wamms, Veronice Oliveira Cristo (2015)
Miguel Sanches Neto appropriates the appeal of hybridism of language, literature and history together to contemplate the narrative of the saga of immigrants who come to Brazil, in 1890, to speak of a polyandrous romance between three men and one woman. However, to do this by the memory resource of historical and fictional characters, the author reveals how the literary plot backdrop the discourses surrounding issues such as power relationships between the subject of the narrative with their peers and the confrontation of these individual-duos with the ideologies of family, religion and the Estate, all representative of a dominant cultural power. And it is through this paradox of the desire for unification and nationalization of a group of people so different from each other around a common ideal that stands out the atmosphere of conflict between the subject and their identities. The present dissertation discusses on the discursive relationship between language and the concept of nationalism as constituting the identity of a people, from the observation of the narrative of Miguel Sanches Neto (2005), by intersecting the historical-documentary discourse with the fictional one, as well as the relationship of the work with dialogic processes that fuses literature and history to build the concept of nationality, from the deconstruction of the past as a way of interpreting the present. The analysis of the literary sense effects introduces for its narrative construction, as well as through it point out the places where they reproduce the processes of domination still recurring in contemporary society. The narrative language employed by Miguel Sanches Neto reveals speeches that conflict the ideal of an egalitarian and fraternal nation with discourses that spread ideological reflects of the dominant culture, such as subjectivity, individualism, private property. It is therefore as Linda Hutcheon (1991, p. 35) a form of "questioning the relationship between history and reality about the relationship between reality and language". On the other hand, from the point of view of the recollection of the past, the national author, unlike nostalgic novels, represents in this work a critical vision of that past, as affirms Lukács (2009) "exhuming the buried sense" or as White (1994) deconstructing the "petrified" directions in social memory.